Cancer of the respiratory tract in nickel sinter plant workers: effect of removal from sinter plant exposure. Issue 1 (January 1994) - Muir, D C; Jadon, N; Julian, J A; Roberts, R S
Abstract : The risk of death due to cancer of the nose or lung was studied in nickel sinter plant workers during the period after they left the sintering operations. It was found that the excess risk of death from both diseases continued for many years after leaving the sinter plant. No effect of age at first exposure could be found. Possible explanations for the continued risk include an irreversible cellular change or the persistence of carcinogenic nickel compounds in the mucosa.